Credit Card Transaction System Using Secured Software (Journal of Information Technology and Digital World, 2024)
The Credit Card Transaction System, is developed using the XAMPP server-a combination of Apache, MySQL, Perl, and PHP-is a dependable and secure financial software solution. For seamless credit card transactions, this system places a strong emphasis on functionality and security. The Apache web server ensures user accessibility by enabling the online application to be hosted on a stable platform. MySQL, a relational database management system, securely stores and manages sensitive data, protecting its security and integrity. The program integrates PHP and Perl scripts to process payments, which is one of its primary features. PHP is a programming language on the server side that handles the dynamic aspects of the website, ensuring efficient data exchange between the database and user interface. Perl scripts offer a range of server-side functions that enhance system functionality, making transaction processing more comprehensive and responsive. The NodeMCU, acting as the backend system's central processing unit, manages communication with the RFID Module RC522. The RFID Module RC522, which enables customers to initiate with their respective RFID cards resembles a credit card in this prototype. Each RFID card has a unique identification number that paves the way to diverse customer access and usage. This reliable hardware configuration makes very little effort required to process the payments. The main objective of developing this prototype is to enhance the safety and security environment of the existing credit card system by adding personal questions that have to be answered by the payment maker to complete the transaction. It is almost impossible to crack the personal questions stage with advanced algorithms, mathematical techniques etc, because it is only known to the authorized user of the card. Although the frauds and thefts involving credit cards occur only in small percentages around 1%-3%, the volume of payments involved is huge when compared to credit cards. Thus, resulting in a large sum of money that has been misused by the fraudsters. Hence to protect this, the proposed system has suggested a novel method for the implementation of the small and safe system to proceed with payments. This little and effective feature keeps away hackers from accessing others' credit cards and prevents speculation.
Keywords: XAMPP Server; Processing unit; Personal question; NodeMCU; RFID